Farid al-Thariqah al-Qiyasiyyah fi Ta’lim Qawa’id al-Lughah al-‘Arabiyyah li al-Nathqin bi Ghairiha fi al-Madaris al-Islamiyyah - Maujud, Fathul; Handriawan, Dony; Patriawati, Septi; Nurman, Muhammad; Eldin Saaid, Alaa Salah (Arabiyatuna: Jurnal Bahasa Arab, 2023)
This research aimed to find out: 1) the process of applying the measurement method to learning Arabic grammar in one of the secondary schools in Lombok for the students of class X at Madrasah Aliyah Nida’urrahman Bebie; and 2) the difficulties in applying the qiyasi method to learning Arabic grammar for students in class X at Madrasah Aliyah Nida’urrahman Bebie. As a whole, researchers tried to find the uniqueness of the qiyasi method, while the measurement method was one applied in learning Arabic, especially in learning Arabic grammar in class X at Madrasah Aliyah Nida’urrahman. It is not known whether the method is suitable for all students, considering that this method is more suitable for use at the upper level or university level, whereas students at Madrasa Nida’urrahman come from various educational backgrounds, including beginner-level students. This research employed a descriptive-qualitative method. Data collection techniques included observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results fell into the following: 1) The process of applying the measurement method in learning Arabic grammar in class X Madrasah Aliyah Nida’urrahman Bebie demonstrated some information. The teacher repeated the lesson from the previous week, explained certain grammar, and gave examples. Hence, with these examples, the teacher explained the rules in more detail. After it was deemed sufficient, the teacher asked students to work in questions from the book to find out the extent of their understanding of materials that had been explained. 2) The obstacles in the application of the measurement method in class X Madrasah Aliyah Nida’urrahman Bebie subsumed (a) the obstacles faced by the teacher, namely the different backgrounds of students, and environmental factors; and (b) the obstacles faced by students covering a lack of knowledge, boredom when studying, and sleepiness when studying.